Modeling and assessment of the efficiency of horizontal and vertical ground heat exchangers - Florides, Georgios A.; Iosif-Stylianou, Iosifina; Tassou, Savvas A.; Zomeni, Zomenia; Tsiolakis, Efthymios; Pouloupatis, Panayiotis; Kalogirou, Soteris A.; Christodoulides, Paul; Messaritis, Vassilios; Panagiotou, Gregoris; Theofanous, Elisavet (My University, 2013)
This paper describes the mathematical modeling of vertical and horizontal GHEs (ground heat exchangers) and compares their efficiency. The model used calculates the heat flow in the fluid, tubes, grout and ground. The vertical U-tube GHE is represented by two 100 m lines, embedded in four different types of ground with an additional bottom base. The horizontal GHE consists of four 50 m tube lines embedded in three ground layers. The initial ground temperature for all cases examined matches real data acquired in June at a location in Cyprus and the simulation results for the vertical GHE are validated using measured data showing very good agreement. Further simulations with the vertical GHE show that when the initial ground temperature rises, the mean temperature of the GHE fluid increases proportionally. Comparisons between horizontal and vertical GHEs reveal that under the same operating conditions and center-to-center distances of the tubes, the vertical GHE keeps a much lower mean temperature. Simulations for a horizontal GHE, for a 50-h of continuous operation period and 24 °C initial ground temperature, show that the mean fluid temperature can remain lower than that of the vertical GHE if the center-to-center distance of the tubes increases to 1 m.
Keywords: Horizontal GHE (ground heat exchanger); Vertical GHE; Modeling; Heat pumps